2012
DOI: 10.1371/journal.pone.0028203
|View full text |Cite
|
Sign up to set email alerts
|

Serum Starvation Induced Cell Cycle Synchronization Facilitates Human Somatic Cells Reprogramming

Abstract: Human induced pluripotent stem cells (iPSCs) provide a valuable model for regenerative medicine and human disease research. To date, however, the reprogramming efficiency of human adult cells is still low. Recent studies have revealed that cell cycle is a key parameter driving epigenetic reprogramming to pluripotency. As is well known, retroviruses such as the Moloney murine leukemia virus (MoMLV) require cell division to integrate into the host genome and replicate, whereas the target primary cells for reprog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 44 publications
4
88
0
2
Order By: Relevance
“…This is in agreement with previous reports of CDK4/6 inhibition leading to sequential emptying of the cell-cycle phases downstream of the restriction point, followed by an increasing spread of cells across phases upon release from synchronization (11,24,25). It should be pointed out, however, that using the same rate constant between each transit compartment would not have accounted for the different duration of each cell-cycle phase (17,26,27).…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with previous reports of CDK4/6 inhibition leading to sequential emptying of the cell-cycle phases downstream of the restriction point, followed by an increasing spread of cells across phases upon release from synchronization (11,24,25). It should be pointed out, however, that using the same rate constant between each transit compartment would not have accounted for the different duration of each cell-cycle phase (17,26,27).…”
Section: Discussionsupporting
confidence: 92%
“…1B). These findings are in agreement with those of a previous study, which found that the highest proportion of cells were in S phase after 20 h of refeeding of serum (27). While the actual percentage of cells in each phase was different by using immunofluorescence, our analysis of the cell cycle using the S-phase-specific marker BrdU (28) showed a similar pattern, with the highest percentage of cells being in S phase after 16 h.…”
Section: Discussionsupporting
confidence: 92%
“…All experiments were performed using media containing 1% serum following 24 h of serum starvation. This procedure has been effective for the synchronization of cells in the G0 phase in cell cycle studies (22,23).…”
Section: Methodsmentioning
confidence: 99%